HASIL TES URINE DALAM PEMBUKTIAN TINDAK PIDANA NARKOTIKA YANG DILAKUKAN OLEH OKNUM ANGGOTA KEPOLISIAN PADA TINGKAT PENYIDIKAN - Roy Capri Tiskartono; Iyah Faniyah; Adhi Wibowo (UNES Journal of Swara Justisia, 2019)
Article 75 of Law Number 35 of 2009 concerning Narcotics regulates the authority of police investigators and the National Narcotics Agency to conduct urine tests on narcotics crimes. The urine test test is intended to ensure the perpetrators consume narcotics so that they can be determined as suspects in criminal acts of narcotics abuse. The role of urine test results in an effort to apply the elements of the article and to prove a narcotics case is very important to be carried out in order to assist investigators in the inspection process and determine someone who is suspected of using narcotics as investigators of the West Sumatra Regional Police Directorate of Investigation cases of narcotics abuse committed by individual members of the National Police.